The plenary council and canon law - Waters, Ian (The Australasian Catholic record, 2018)
The Australian hierarchy was established by Pope Gregory XVI in 1842. Since then, there have been six national Catholic councils held in Australia. The first two, celebrated in 1844 and 1869, are known as the First Provincial Council of Australia and the Second Provincial Council of Australia, as until 1874 the Australian dioceses were all in the one ecclesiastical province with Sydney being the sole metropolitan see. In 1874, a second province- Melbourne - was established, and the national councils since then - four of them, celebrated in 1885, 1895, 1905 and 1937 - have been called plenary councils, the term used in the Catholic Church in recent centuries for councils whose participants are from more than one ecclesiastical province; in the past, terms such as regional councils or national councils have been used. As we all know, another plenary council for Australia is planned to commence in 2020.